AI-enhanced human resource and green accounting: for achieving sustainable development performance in sharia bank industry - Satria Avianda Nurcahyo; Anisa Dewi Arismaya; Fitri Dwi Jayanti; Anis Malik Thoha (Journal of Islamic Accounting and Finance Research, 2025)
Purpose - The purpose This study investigates the role of AI-enhanced human resources in environmental innovation strategy, green accounting, and sustainable development performance within the state-owned sharia banking sector. Method - Using a quantitative approach and Structural Equation Modeling (SEM) Partial Least Squares (PLS), the research involves a sample of 250 employees from various state-owned sharia banks in Central Java. Result - The results showed indicate that the implementation of AI in human resource management significantly contributes to environmental innovation strategy and green accounting, which in turn supports sustainable development performance. Additionally, green accounting is found to play a critical role in enhancing organizational sustainability performance. Implication - These findings offer valuable insights for strategic policies in the sharia banking sector, aiming to achieve sustainable development goals through the integration of intelligent technology and eco-friendly practices in organizational operations. Originality - This research provides the first insights that serve as a foundation for academics and policymakers to develop more comprehensive models for sustainable development in the sharia banking.